Idiopathic CRMO and MEFV Gene Variant Alleles: Is There Any Relationship? - Salehzadeh, Farhad (Case Rep Rheumatol, 2019)
BACKGROUND AND OBJECTIVE: CRMO is an inflammatory disease of bone that occurs more often in children. The clinical manifestations are intermittent fever, pain, and bone lesions, especially in long bones. Although there is an idiopathic type of disease, it is usually associated with some autoimmune disorders. This study evaluates MEFV gene mutations as background pathology of idiopathic CRMO. METHODS: Blood samples of patients, who diagnosed as childhood idiopathic CRMO by imaging and pathologic study from June 2011 until September 2018, have been screened for the 12 common pathogenic variants of MEFV gene mutations. RESULT: Nine patients enrolled in this study, and eight of them were male. The most common involvement locations were tibia and femur, and the least ones were zygoma, calcaneus, and radius. The mean duration of the involvement was 1.3 years. Six patients had only 1 involved location, 2 patients showed two sites of involvement, and one patient had three affected areas. There were two positive MEFV gene mutations (22%), as E148Q/wt and K695R/wt both in the heterozygote form. There was no meaningful relationship between MEFV gene mutations and the age of onset, gender, and location of involvement. Patients with positive mutation had more involved sites and long duration of involvement significantly. CONCLUSION: There is no significant immunopathogenic relationship between the common MEFV gene variant alleles and CRMO disease.